(untitled) (Architecture Image Studies, 2026)
This research is quantitative and uses an explanatory research design. The population was all 151 employees at the Southeast Sulawesi Provincial DPRD Secretariat. Data collection used a questionnaire distributed directly to respondents. Data analysis used Structural Equation Modeling Partial Least Squares (SEM-PLS) and processed using SmartPLS 4. The results showed that organizational climate significantly influenced innovative behavior (β = 0.091; t = 6.492; p = 0.000) and employee well-being (β = 0.856; t = 9.310; p = 0.000), but not significantly on employee performance (β = -0.086; t = 1.411; p = 0.093). Workplace spirituality significantly influences innovative behavior (β = 0.842; t = 15.579; p = 0.000) and employee performance (β = 0.254; t = 10.598; p = 0.000), but not significantly on well-being (β = -0.491; t = 1.215; p = 0.213). Innovative behavior significantly influences performance (β = 0.021; t = 21.119; p = 0.000) and employee well-being (β = 0.549; t = 8.569; p = 0.000). In the mediation pathway, innovative behavior significantly mediated the effect of spirituality on well-being (β = 0.143; t = 3.911; p = 0.000) and organizational climate on well-being (β = 0.462; t = 3.915; p = 0.000), but did not significantly mediate the effects of spirituality on performance (β = 0.002; t = 0.095; p = 0.924) or organizational climate on performance (β = 0.018; t = 0.667; p = 0.505). Meanwhile, government support was not significant as a moderating variable in the relationship between organizational climate and innovative behavior (β = -0.020; t = 1.179; p = 0.739), thus categorizing it as a homologizer.